The Application of the New Media a Review on Learning Media in the VUCA Era (Open Society Conference, 2023)
In the face of the VUCA age, a generation with critical thinking, analytical and inventive thinking is required. As a result, the purpose of this research is to address the issues of the period of how new media as a digital age learning material for the VUCA era. Using the review materials, it is possible to conclude that in this VUCA era, new interactive learning media that may promote It is necessary for students to have analytical, critical, and creative thinking. Further research is planned to be able to create interactive learning material due to new media that includes discussion places for students and teachers.